Characterization of functional human insulin produced using the Pichia pastoris expression system - Dini Nurdiani, Eko Wahyu Putro, Endah Puji Septisetyani, Nuruliawaty Utami, Hariyatun Hariyatun, Pekik Wiji Prasetyaningrum, Wien Kusharyoto (Journal of Applied Pharmaceutical Science, 2024)
The recombinant yeast Pichia pastoris produced insulin precursor (IP) by secreting it extracellularly. Synthetic prepro-leaders were developed for IP secretory expression in Saccharomyces cerevisiae, and we employed a P. pastoris recombinant clone (CL-4) with a synthetic IP-encoding gene in its genome to generate IP. The secreted IP was analyzed using LC-MS/MS analysis to compare it with the theoretical molecular weight. A pulse-batch method was utilized to produce the IP in a 2 l bioreactor. The purified IP was further converted into mature human insulin (HI) through a one-step transpeptidation reaction. The HI was then subjected to a series of steps including crystallization, deprotection, and purification. The IP purification recovery increased by 90% as compared to our previous study. The mass spectrometry (MS) analysis of the IP yielded an identical theoretical molecular weight value of 7072.10 Da. Furthermore, a specific molecular species of 5839.56 Da was detected by intact MS in the purified 1C5 fraction, which is similar to the oxidized form of HI. Based on our in vitro glucose uptake assay, the 1C5 fraction stimulated glucose uptake at a ratio of 0.86 compared to USP HI, indicating the functional presence of HI in the 1C5 fraction.
Keywords: Bioreactor, glucose uptake assay, human insulin, insulin precursor, Pichia pastoris, transpeptidation